Secure Three-Dimensional Guidance for Target Strikes Under Unknown Direction Attacks and Multiple Constraints - Wang, Yu; Wang, Chenliang; Zhu, Baopeng; Liu, Guowei; Wang, Enmei; Guo, Lei (IEEE transactions on aerospace and electronic systems, 2025)
Due to the high reliance of guidance systems on wireless networks, ensuring the secure operation of missiles under cyber-attacks is critical to avoid degradation in guidance precision or system divergence. In this article, a secure 3-D guidance law is proposed for speed-varying missiles to precisely strike targets under unknown direction cyber-attacks on guidance commands, including falsification of their magnitudes and signs. To improve the lethality while avoiding violation of the seeker's field-of-view limits, the constraints on impact angles and the look angle are both taken into consideration by constructing two auxiliary variables. To attenuate the adverse effects caused by cyber-attacks, Nussbaum functions are employed to search for the attack directions, and adaptive techniques are applied to estimate the unknown attack-related parameters. Moreover, the closed-loop stability of the guidance system can be guaranteed even in the presence of nonidentical attack directions in two guidance channels and malicious sign switchings. Finally, the effectiveness of the proposed scheme is illustrated by simulation results.